2001
DOI: 10.1038/sj.onc.1204275
|View full text |Cite
|
Sign up to set email alerts
|

G-proteins in growth and apoptosis: lessons from the heart

Abstract: The acute contractile function of the heart is controlled by the e ects of released nonepinephrine (NE) on cardiac adrenergic receptors. NE can also act in a more chronic fashion to induce cardiomyocyte growth, characterized by cell enlargement (hypertrophy), increased protein synthesis, alterations in gene expression and addition of sarcomeres. These responses enhance cardiomyocyte contractile function and thus allow the heart to compensate for increased stress. The hypertrophic e ects of NE are mediated thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 107 publications
4
63
0
1
Order By: Relevance
“…Similarly, the various signaling pathways activated by AII have all been implicated in cardiac hypertrophy, apoptosis, or both (1,24,46). Their importance in mediating specific AII effects as well as their involvement in AII regulation of cardiac genes has not been firmly elucidated.…”
mentioning
confidence: 99%
“…Similarly, the various signaling pathways activated by AII have all been implicated in cardiac hypertrophy, apoptosis, or both (1,24,46). Their importance in mediating specific AII effects as well as their involvement in AII regulation of cardiac genes has not been firmly elucidated.…”
mentioning
confidence: 99%
“…Hypertrophy in response to pressure overload involves heterotrimeric G proteins of the G q/11 class (1) and activation of G q is sufficient to cause hypertrophy in vivo (2), as well as in cell models (3). In keeping with this, activation of G q -coupled receptors including ␣ 1 -adrenergic receptors (␣ 1 -AR), 1 ET A receptors or AT 1 receptors on neonatal rat ventricular myocytes (NRVM) causes increased growth of the cardiomyocytes, as well as increasing transcription from "hypertrophic" marker genes, such as ANP and MLC2 (3). Signaling pathways associated with increased protein synthesis, and hence cell size, are known to be partly independent of those causing re-expression of ANP and MLC2, but both can be activated by G q (4).…”
mentioning
confidence: 99%
“…G␣ q/11 is a well-established mediator of cardiac hypertrophy, 10 so we hypothesized that G-protein coupling to the Figure 4A). 17 [Y215F]AT 1 was confirmed as a G proteinuncoupled mutant with robust expression ( Figure S2 and Table S1) and, although [Y215F]AT 1 was described previously with reduced radioligand affinity, we found no statistically significant difference in affinity compared with WT, and the Ang II concentrations used herein are sufficient to ensure almost complete receptor occupancy at either receptor.…”
Section: G-protein Coupling Is Required For Egfr Transactivation and mentioning
confidence: 99%
“…Recent studies suggested a G protein-independent pathway for growth activation, 6 -9 despite evidence that G␣ q/11 , a heterotrimeric G protein that couples to the AT 1 R, is essential for hypertrophy. 10 Indeed, others indicate that G-protein coupling to AT 1 R is required for EGFR transactivation in COS-7 and vascular smooth muscle cells. [11][12][13] Meanwhile, evidence for ␤-arrestin-dependent functional selectivity of the Ang II analog sarcosine, 1 isoleucine, 4 isoleucine, 8 Ang II (SII Ang II), 14 ␤-arrestin-mediated EGFR transactivation by ␤ 1 -adrenoceptors independent of G-protein coupling, 15 and the very recent demonstration of ␤-arrestin-dependent hypertrophy resulting from mechanical stretch 16 suggests that ␤-arrestin scaffolding of extracellular signal-regulated kinase (ERK) 1/2 may contribute to transactivation and/or cardiac hypertrophy.…”
mentioning
confidence: 99%